Mitochondrial DNA variability of Octopus vulgaris (Mollusca, Cephalopoda) in the Tunisian Waters - Nafkha, Basma; Ezzeddine, Soufia; Fadhlaoui-Zid, Karima (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
This study provides data on the genetic structuring of Octopus vulgaris in the Tunisian waters. A total of 121 specimens were collected in four locations (one in the western Mediterranean and three in theCentral Mediterranean). A portion of the cytochrome b gene (485pb) of the mitochondrial DNA was analysed. The most relevant result was the high genetic structuring among populations in the study area (Î¦ST = 0.06851, p <0.0001). Median-joining network analysis did not separate any haplotype group, and haplotype distribution did not mirror the geographic origin of the samples. Populations pairwise Î¦ST and MDS analyses clearly showed that the populations from the coast are differentiated from the deep sea populations. For purposes of stock management, these two groups should be considered as separate stocks.